2016
DOI: 10.1093/hmg/ddw269
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive expression of MeCP2 in the nervous system distinguishes between brain and peripheral Rett syndrome-like phenotypes

Abstract: Rett syndrome (RTT) is a severe genetic disorder resulting from mutations in the X-linked MECP2 gene. MeCP2 protein is highly expressed in the nervous system and deficiency in the mouse central nervous system alone recapitulates many features of the disorder. This suggests that RTT is primarily a neurological disorder, although the protein is reportedly widely expressed throughout the body. To determine whether aspects of the RTT phenotype that originate in non-neuronal tissues might have been overlooked, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 76 publications
2
62
0
Order By: Relevance
“…50,51 Deletion of Mecp2 from glia in mice has relatively minor phenotypic consequences but a restoration of MeCP2 to astrocytes in an otherwise MeCP2-deficient nervous system results in a partial amelioration of phenotypes including a normalisation of breathing patterns, motor activities and anxiety. 48 As also indicated in primary culture experiments, 52 MeCP2 in glial cells may contributing to certain non-cell autonomous functions such as supporting normal dendritic morphology through the release of trophic factors within the nervous system.…”
Section: Mecp2 Is Essential For Normal Brain Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Deletion of Mecp2 from glia in mice has relatively minor phenotypic consequences but a restoration of MeCP2 to astrocytes in an otherwise MeCP2-deficient nervous system results in a partial amelioration of phenotypes including a normalisation of breathing patterns, motor activities and anxiety. 48 As also indicated in primary culture experiments, 52 MeCP2 in glial cells may contributing to certain non-cell autonomous functions such as supporting normal dendritic morphology through the release of trophic factors within the nervous system.…”
Section: Mecp2 Is Essential For Normal Brain Functionmentioning
confidence: 99%
“…61 Overall, MeCP2 depletion studies have revealed that the majority of Rett syndrome-like behavioural, sensorimotor and autonomic phenotypes associated with are MeCP2 deficiency in the brain but that that some less extreme but clinically significant aspects of the disorder may arise independently of defects in the nervous system. 51 …”
Section: Mecp2 In Non-neural Cellsmentioning
confidence: 99%
“…Wild type and MECP2 deficient mice were then compared and it was shown that the majority of neurological symptoms were absent. However bone abnormalities, fatigue, and hypo-activity was observed, which confirms brain as the primary organ for MECP2 associated phenotypes, but it also suggests that less extreme form of disorder may arise independent of the nervous system (Ross et al, 2016).…”
Section: Mecp2expression In Central Nervous System (Cns)mentioning
confidence: 68%
“…Since dendritic spines are the locations of excitatory synapses, a consequence of Mecp2 deficiency is reduced synaptic number and functional connectivity (Chao et al 2007;Chapleau et al 2009). However, MECP2's expression outside the nervous system leads to a number of systemic problems, including metabolic syndrome (Kyle et al 2016;Ross et al 2016;Kyle et al 2018).…”
Section: Introductionmentioning
confidence: 99%